Analisis Pemanfaatan Sumber Informasi Dan Tingkat Pengetahuan Petani Tentang Usahatani Sayur Bayam Di Desa Walay Kecamatan Abuki Kabupaten Konawe - Suryani Khalzum; Iskandar Zainuddin Rela; Salahuddin Salahuddin (Jurnal Ilmiah Penyuluhan dan Pengembangan Masyarakat, 2021)
The background of the research was the use of farmer information sources in increasing farmers' knowledge about spinach farming. This study aims to determine the usefulness of farmers' information sources and the level of expertise in spinach farming. As well as seeing the relationship between the use of information sources and the level of knowledge of farmers about spinach farming. This study uses a quantitative descriptive method with 45 farmers as respondents. Rank spearman is used data analysis in this study. The results showed that the use of information sources was categorized as moderate. The information sources that farmers mostly used were fellow farmers, and the least came from agricultural extension workers. The level of knowledge of farmers in spinach farming in spinach farming is in the medium category. There is a significant relationship between the use of information sources and the level of knowledge of farmers in Walay Village, Abuki District, Konawe Regency.